LENDING GROWTH AS A FIQH IMPLICATION TOWARD PRODUCT DEVELOPMENT OF ISLAMIC BANK IN INDONESIA - Prasetyowati, Riris Aishah (INOVATOR, 2017)
This study aim to examine the financing growth of Islamic bank in Indonesia with the provisions system and proof that there is a procyclicality and income smoothing behavior of bank manager. The objects of this study are Islamic Banks and Islamic Business Unit in Indonesia period of 2000 – 2016. This study specifically estimates a different calculation in every component of discretionary and non-discretionary in Islamic bank financing with the variable controlsuch as deposit growth, equity ratio, and total asset. The equation will be tested by using the regression system estimation and the validity tested by AR and Hansen test. The result of this study quantitatively proved that there is a pattern of procyclicality behavior in Islamic bank consistent with hypothesis and significantly has negative correlation described by the relation of loan loss provision with the coefficient of GDP growth rate: -0,207. From this result in accordance with the fiqh platform, for all forms of muamalah is “al ashlufilmu?amalahilla al-ibahahyadulludaliil „alaatahriimiha” (the origin of everything is allowed unless there is proof that forbid it), which means that by using the theory of fiqh rules the product development of Islamic bank can be done and expanded.